Effect of Enforcement Shock on Pushers' Activities: Evidence from an Asian Drug-Selling Gang - Kaiwen Leong; Huailu Li; Haibo Xu (Institute of Labor Economics (IZA), 2019)
We study a Singaporean drug-selling gang's dataset and empirically find that the gang's pushers purchased larger quantities of drugs during periods of enforcement shocks caused by enforcement activities targeting the gang's drug supply chain. This counter-intuitive finding can be explained by the pushers' profit targeting behavior. Given that enforcement shocks increased the pushers' cost of drugs, pushers must compensate by purchasing more drugs to sell in order to reach their profit targets.
Keywords: J46; K42; 330; crime; enforcement; labor supply